A Descriptive Study On Teaching Speaking At The Tenth Grade Of Office Administration Department At SMK N 1 Banyudono In 2015/2016 Academic Year - Haffi, I Rhizal Umami; , Drs. Djoko Srijono M. Hum (2016)
This study aims at describing the technique used by the teacher in teaching-learning process of speaking, the problems faced by the English teacher and the students, and the way teacher and students solves the problems in teaching-learning speaking at the tenth grade of Office Administration Department. The writer uses descriptive qualitative research. The subject of this study is the English teacher and the tenth grade students of Office Administration Department. The methods of collecting data are observation, content of document analysis, and interview. In analyzing data, the writer uses an interactive model, namely, data reduction, data display, and verification of the data. Based on the research finding, the teacher used discussion in teaching speaking, while the procedures on teaching speaking skill are; 1) opening, 2) choral imitation, 3) individual imitation, 4) assignment, 5) presentation, 6) evaluation, and 7) closing. But the teacher did not always use all of the teaching procedures. The problems faced by the teacher are; 1) the limited time in speaking teaching-learning process, 2) the different capability of the students. The problems faced by the students are; 1) lack of vocabulary, 2) got difficulty in pronouncing the word, 3) got difficulty in spelling the word, and 4) being afraid of making mistakes. The strategies to solve the problems faced by the English teacher in teaching-learning speaking are; 1) making a summary or the points, 2) giving some opportunities to the students to ask something. The strategies to solve the problems faced by the students in teaching-learning speaking are; 1) bringing a dictionary, 2) practicing frequently, 3) reading an English book, and 4) learning from their mistakes. Keywords: problems faced by the teacher and the students, strategies to solve the problems, speaking skill, technique used during teaching-learning process in speaking